KOMBINASI VIGENERE CIPHER DAN POLYALPHABETIC CIPHER PADA PENGAMANAN FILE TEXT - Elvin Tarigan; Denny H.S. Maha (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2018)
Cryptography is the art of securing message security. The purpose of this research is to produce an encryption and decryption application to secure text messages by combining the two methods of cryptographic Vigenere Cipher and Polyalphabetic Cipher. When the encryption and decryption process occur, you should first enter the plaintext and key to run the program. In designing this application using the Visual Studio 2010 programming language. Through this application the user can Combine Vigenere Cipher with Polyalphabetic Cipher and produce encryption and decryption of a text or sentence. In the encoding process has a specified character limit of 200 characters. Plaintext is divided into 1 block consisting of 3 characters. In this combination application uses 3 keys. The key is not allowed to have repeated letters. The results of encryption and decryption will result in spaces in the sentence.